Urban balcony gardens: exploring a resident-led nature-based solution - Salma N. Talhouk; Carine Ghassibe; Samar Morkos; Dany Abou Jaoude; Ibrahim Issa (Urban Ecosystems, 2026)

Pantoea dispersa from olive pomace compost suppresses Pythium aphanidermatum damping-off in Cucumis sativus - Ikhlass Al-Shaqsi; Yahya Al-Fahdi; Issa Hashil Al-Mahmooli; Ibrahim Al-Khusaibi; Ahmed Al-Fahdi; Abdullah Mohammed Al-Sadi; Rethinasamy Velazhahan (Indian Phytopathology, 2025)

Identification of moving sources in stochastic flow fields: A bayesian inferential approach with application to marine traffic in the mediterranean sea - Issam Lakkis; Alexios Rustom; Mohamad Abed El Rahman Hammoud; Leila Issa; Omar Knio; Olivier Le Maitre; Ibrahim Hoteit (Computational Geosciences, 2025)

Biosynthesis of trimetallic nanoparticles and their biological applications: a recent review - Amr H. Hashem; Ebrahim Saied; Bahaa M. Badr; Mohamed Soliman Dora; Mahmoud A. Diab; Amer Morsy Abdelaziz; Fathy M. Elkady; Mohamed Abdelrahman Ali; Nasser Ibrahim Issa; Ziad A. Hamdy; Mohamed E. Nafea; Ahmed Nageh Khalifa; et al. (Archives of Microbiology, 2025)

Epigallocatechin gallate-rich fraction alleviates histamine-induced neurotoxicity in rats via inactivating caspase-3/JNK signaling pathways - Eman I. Hassanen; Hayam A. Mansour; Marwa Y. Issa; Marwa A. Ibrahim; Wafaa A. Mohamed; Mahmoud A. Mahmoud (Food and Chemical Toxicology, 2024)

The Azawak zebu bred at the Toukounous experimental centre in Niger: reproduction performance and estimation of genetic parameters - Adamou Karimou Ibrahim; Issa Moumouni; Chanono Mogueza (Tropical Animal Health and Production, 2024)

Determination of polycyclic aromatic hydrocarbons (pahs) in mothers’ milk of kafr el-zayat district, egypt: A case study for the health risk of infants in urban regions - Asmaa Bayoumi Issa; Helmy Aly Ibrahim Anber; Sobhy Abdel-Rahiem Hamed; Fayza Ahmed Seddik; Khaled Yassin Abdel-Halim (Environmental Monitoring and Assessment, 2024)

Morphological adaptation to environmental stress in small ruminants from the sahelian zones of Niger and potential associations with carcass yield - Ibrahim Adamou Karimou; Hassane Yaye Abdou; Issoufou Guero Chekaraou; Moumouni Issa (Journal of Thermal Biology, 2024)

A cost-benefit analysis of ecosystem services from restoring degraded soils to forest ecosystems in the Sahel - Sibiry Albert Kaboré; Emmanuelle Quillérou; Stéphanie Maiga-Yaleu; Maguette Kairé; Ibrahim Bouzou Moussa; Oumarou Malam Issa; Damien Hauswirth; Hassan Bismarck Nacro (Journal for Nature Conservation, 2024)

MicroRNA mmu-miR-511-5p: A promising Diagnostic Biomarker in Experimental Toxoplasmosis Using Different Strains and Infective Doses in Mice with Different Immune States Before and After Treatment - Rasha Fadly Mady; Mona Mohamed El-Temsahy; Yasmine Amr Issa; Aya Saied Zaghloul; Safaa Ibrahim Khedr (Acta Parasitologica, 2024)
Purpose Searching for a novel early diagnostic biomarker for toxoplasmosis, real-time-PCR was currently used to measure the serum mmu-miR-511-5p level in male Swiss-albino mice infected with either; ME49 or RH Toxoplasma gondii ( T. gondii ) strains. Methods Three mice groups were used; (GI) constituted the non-infected control group, while (GII) and (GIII) were experimentally infected with ME49 or RH strains, respectively. GII mice were orally infected using 10 or 20 ME49 cysts (ME-10 and ME-20), both were subdivided into; non-treated (ME-10-NT and ME-20-NT) and were further subdivided into; immunocompetent (ME-10-IC and ME-20-IC) [euthanized 3-days, 1, 2, 6 or 8-weeks post-infection (PI)], and immunosuppressed using two Endoxan ® injections (ME-10-IS and ME-20-IS) [euthanized 6- or 8-weeks PI], and spiramycin-treated (ME-10-SP and ME-20-SP) that received daily spiramycin, for one-week before euthanasia. GIII mice individually received 2500 intraperitoneal RH strain tachyzoites, then, were subdivided into; non-treated (RH-NT) [euthanized 3 or 5-days PI], and spiramycin-treated (RH-SP) that were euthanized 5 or 10-days PI (refer to the graphical abstract). Results Revealed significant upregulation of mmu-miR-511-5p in GII, one-week PI, with gradually increased expression, reaching its maximum 8-weeks PI, especially in ME-20-NT group that received the higher infective dose. Immunosuppression increased the upregulation. Contrarily, treatment caused significant downregulation. GIII recorded significant upregulation 3-days PI, yet, treatment significantly decreased this expression. Conclusion Serum mmu-miR-511-5p is a sensitive biomarker for early diagnosis of ME49 and RH infection (as early as one-week and 3-days, respectively), and its expression varies according to T. gondii infective dose, duration of infection, spiramycin-treatment and host immune status. Graphical abstract

Mechanical characterisation of the stones of Notre-Dame de Paris by in situ acoustic velocity measurement - Nathalie Domede; Thomas Parent; Colin Guenser; Ali Boukham; Pierre Morenon; Aboubacar Sadikou Issa-Ibrahim (International Journal of Rock Mechanics and Mining Sciences, 2024)

Comprehensive review on the efficiency of ionic liquid materials for membrane separation and environmental applications - Weidong Li; Duaa Abdul Rida Musa; Nafis Ahmad; Mohaned Adil; Usama S. Altimari; Abdullah Khaleel Ibrahim; A.M. Alshehri; Yassin Riyahi; Asala Salam Jaber; Sokaina Issa Kadhim; Anastasia Andreevna Rushchitc; Mutlaq Owaidh Aljuaid (Chemosphere, 2023)

An atypical expression of core α-Dystroglycan and Laminin-α2 in skin fibroblasts of patients with congenital muscular dystrophies - Sahar Sabry; Mahmoud Y Issa; Mohamed S Abdel-Hamid; Noura R Eissa; Sherif F Abdel-Ghafar; Mona M Ibrahim; Maha S Zaki (Molecular Biology Reports, 2023)
Background Congenital muscular dystrophies (CMDs) result from genetically inherited defects in the biosynthesis and/or the posttranslational modification (glycosylation) of laminin-α2 and α-dystroglycan (α-DG), respectively. The interaction between both proteins is responsible for the stability and integrity of the muscle cell. We aimed to study the expression profiles of both proteins in two classes of CMDs. Subjects and methods Whole-exome sequencing (WES) was done for four patients with neuromuscular manifestations. The expression of core α-DG and laminin-α2 subunit in skin fibroblasts and MCF-7 cells was assessed by western blot. Results WES revealed two cases with nonsense mutations; c.2938G > T and c.4348 C > T, in LAMA2 encodes laminin-α2. It revealed also two cases with mutations in POMGNT1 encode protein O-mannose beta-1,2-N-acetylglucosaminyltransferase mutations. One patient had a missense mutation c.1325G > A, and the other had a synonymous variant c.636 C > T. Immunodetection of core α-DG in skin fibroblasts revealed the expression of truncated forms of core α-DG accompanied by reduced expression of laminin-α2 in POMGNT1-CMD patients and one patient with LAMA2-CMD. One patient with LAMA2-CMD had overexpression of laminin-α2 and expression of a low level of an abnormal form of increased molecular weight core α-DG. MCF-7 cells showed truncated forms of core α-CDG with an absent laminin-α2. Conclusion A correlation between the expression pattern/level of core α-DG and laminin-α2 could be found in patients with different types of CMD.

Late Pleistocene travertine deposits in the Jordan Valley—Dead Sea area: lithofacies, sedimentological properties and depositional environments - Issa M. Makhlouf; Khalil M. Ibrahim; Ali R. El Naqah; Sana’ M. Al-Thawabteh (Arabian Journal of Geosciences, 2023)

Bioactive phenolic components and antioxidant activities of water-based extracts and flavonoid-rich fractions from Salvadora persica L. leaves - Issa Issoufou Ibrahim; Ag Arya Moussa; Zhuo Chen; Jun Zhang; Wei-Guo Cao; Chao Yu (Natural Product Research, 2022)

Co-circulation of genotypes XIV.2 and XVIII.2 of avian paramyxovirus-1 (Newcastle disease virus) in backyard poultry in Niger - Maman Moutari Souley; Abdoulkarim Issa Ibrahim; Bachir Souley Kouato; Alassane Abdou; Rahila Issa; Bachir Yaou; Hadiza Amadou; Hama Hama; Hassane Adakal; Nourou Abdou; Giovanni Cattoli; William G. Dundon (Virus Genes, 2021)

A literature-based study on the water–energy–food nexus for sustainable development - José Baltazar Salgueirinho Osório de Andrade Guerra; Issa Ibrahim Berchin; Jessica Garcia; Samara da Silva Neiva; Ana Valquiria Jonck; Rafael Avila Faraco; Wellyngton Silva de Amorim; João Marcelo Pereira Ribeiro (Stochastic Environmental Research and Risk Assessment, 2021)

Sanitary quality improvement of fish produced in the northern Benin cotton basin water reservoirs by cage culture and fish transfer in agricultural contaminant-free water: human health implications - Rodrigue O. E. Pèlèbè; Ibrahim Imorou Toko; Issa N. Ouattara; Ulbad P. Tougan; Eloi Y. Attakpa; Jean Fall; Elie Montchowui (Tropical Animal Health and Production, 2020)

Thermal maturity and hydrocarbon generation of the Dawi Formation, Belayim Marine Oil Field, Gulf Of Suez, Egypt: a 1D Basin Modeling Case Study - Mohamed Moustafa Afife; Mohamed Abu Al-Atta; Mohammed A. Ahmed; Ghalib Ibrahim Issa (Arabian Journal of Geosciences, 2016)

A 3-year long study of Staphylococcus aureus isolates from subclinical mastitis in three Azawak zebu herds at the Sahelian experimental farm of Toukounous, Niger - Abdoulkarim Ibrahim Issa; Jean-Noël Duprez; Rianatou Bada-Alambedji; Mamane Djika; Jacques Georges Mainil; Marjorie Bardiau (Tropical Animal Health and Production, 2016)